Central giant cell lesions with an unusual behavior in patient with Noonan syndrome: A case report with 8-year follow-up (Research, Society and Development, 2021)
This study describes a patient with Noonan syndrome affected by multiple Central Giant Cell Lesions (CGCL) in jaws. The lesions presented an unusual behavior since there was no regression size after puberty. The syndrome was diagnosed by collecting clinical information, represented by ocular hypertelorism, low insertion of ears, pulmonary stenosis, cryptorchidism, cardiac abnormalities, short stature, multiple CGCL in the jaws, and blood analysis that found a mutation of the PTPN11 gene. The treatment consisted of systemic calcitonin for a period of 14 months and three surgical procedures at distinct moments. The patient is currently with 20 years and in the eighth-year of follow-up. Although he presented an improvement in deformity, radiological findings showed remodeling without resolution of mandibular injuries, making it clear that injuries will did not always regress after puberty and not confirm previously publications in the literature. We therefore advocate a larger time of follow-up before patient discharge in these cases.